Atypical Presentation of Clinically Non-Functioning Pituitary Macroadenoma: Case Report of Concurrent Graves' Disease and Multi-Axis Pituitary Hypofunction in a 40-Year-Old Female - Rizkha Amaliya; Dolly Irfandy; Hesty Lidya Ningsih; Alexander Kam; Mardijas Efendi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Non-functioning pituitary adenomas (NFPAs) present variable clinical manifestations depending on tumor size and location. Concurrent primary autoimmune thyroid disease in NFPA patients is exceptionally rare and requires careful diagnostic distinction from secondary hypothyroidism. Case presentation: A 40-year-old female presented with progressive bilateral peripheral vision narrowing over 3 months, chronic bifrontal headaches, secondary amenorrhea, and nocturia-predominant polyuria. Neuro-ophthalmologic examination revealed bitemporal hemianopsia with visual acuity 20/200 left eye and 20/25 right eye. Endocrine evaluation demonstrated: primary hyperthyroidism (TSH 0.02 µIU/mL, FT4 28.32 pmol/L, positive thyroid receptor antibodies), secondary adrenal insufficiency (cortisol 1 µg/dL, ACTH <5 pg/mL), and hypogonadotropic hypogonadism (LH 1.62 IU/L). Neuroimaging revealed a 2.13 × 2.28 × 3.05 cm sellar/suprasellar lesion with optic chiasm compression (Knosp Grade II). Endoscopic transsphenoidal surgery achieved complete gross total resection. Histopathology confirmed null-cell adenoma with low Ki-67 proliferation index (2%). Conclusion: Postoperative course was uncomplicated with rapid visual field improvement, complete resolution of bitemporal hemianopsia by 2 weeks, and normalization of all endocrine axes by 12 weeks, including menstrual recovery and gonadal axis restoration. This case illustrates the diagnostic challenge of distinguishing secondary hyperprolactinemia from primary prolactinoma in NFPA, the rarity of concurrent Graves' disease with pituitary macroadenoma, and favorable outcomes with complete surgical decompression achieving multisystem endocrine recovery.